Silanediol Anion Binding and Enantioselective Catalysis - Attard, Jonathan W.; Osawa, Kohei; Guan, Yong; Hatt, Jessica; Kondo, Shin-ichi; Mattson, Anita (Synthesis, 2019)
Silanediols possess unique and complementary catalytic activity in reactions that are likely to proceed through anion binding. This article directly compares silanediols, thioureas, and squaramides in three separate anion-binding processes. The catalytic abilities of select members of each family are directly correlated to association constants.
Keywords: anion recognition; enantioselective catalysis; thiourea; silanediol; squaramide